2022
DOI: 10.1016/j.apmr.2021.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Shadow Pandemic: COVID-19 Related Impacts, Barriers, Needs, and Priorities to Health Care and Support for Women Survivors of Intimate Partner Violence and Brain Injury

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
(27 reference statements)
0
12
0
1
Order By: Relevance
“…When it comes to survivors’ needs during the pandemic, studies reported survivors’ challenges to meeting their basic needs, such as housing (i.e., safe and affordable shelter), accessing technology, transportation, employment, and childcare ( Ragavan et al, 2022 ; Toccalino et al, 2022 ). Importantly, Toccalino et al (2022) emphasized survivors’ need for peer support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to survivors’ needs during the pandemic, studies reported survivors’ challenges to meeting their basic needs, such as housing (i.e., safe and affordable shelter), accessing technology, transportation, employment, and childcare ( Ragavan et al, 2022 ; Toccalino et al, 2022 ). Importantly, Toccalino et al (2022) emphasized survivors’ need for peer support.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to survivors’ needs during the pandemic, studies reported survivors’ challenges to meeting their basic needs, such as housing (i.e., safe and affordable shelter), accessing technology, transportation, employment, and childcare ( Ragavan et al, 2022 ; Toccalino et al, 2022 ). Importantly, Toccalino et al (2022) emphasized survivors’ need for peer support. The stakeholders interviewed reported survivors’ desire to connect with someone “who truly understands their experience” and “the various systems and structures a survivor must navigate from the survivor perspective.” Our study findings echo the same needs of survivors for emotional and informational support, such as wanting to hear about similar experiences from peers, asking for legal advice, needing the validation of their feelings/reactions/thoughts/actions, acknowledging the experience of IPV, and asking for ways to grieve, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also help identify more targeted linkage and immediate options. Research of this nature is especially important given the increasing rates of IPV since the COVID-19 pandemic (Toccalino et al, 2022), which could further complicate linkage efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has exacerbated IPV globally, significantly increasing both rates of IPV and the level of violence per encounter (7)(8)(9)(10)(11). Physical violence in IPV most commonly results in injury to the head, face, and neck (12), leaving survivors at high risk of traumatic brain injury (TBI).…”
Section: Introductionmentioning
confidence: 99%